Three-terminal resistive switch based on metal/metal oxide redox reactions - Mantao Huang (Nature Portfolio, 2017)
Abstract A solid-state three-terminal resistive switch based on gate-voltage-tunable reversible oxidation of a thin-film metallic channel is demonstrated. The switch is composed of a cobalt wire placed under a GdOx layer and a Au top electrode. The lateral resistance of the wire changes with the transition between cobalt and cobalt oxide controlled by a voltage applied to the top electrode. The kinetics of the oxidation and reduction process are examined through time- and temperature-dependent transport measurements. It is shown that that reversible voltage induced lateral resistance switching with a ratio of 103 can be achieved at room temperature. The reversible non-volatile redox reaction between metal and metal oxide may provide additional degrees of freedom for post-fabrication control of properties of solid-state materials. This type of three-terminal device has potential applications in neuromorphic computing and multilevel data storage, as well as applications that require controlling a relatively large current.